2017
DOI: 10.1111/tbj.12945
|View full text |Cite
|
Sign up to set email alerts
|

Breast education for schoolgirls; why, what, when, and how?

Abstract: Schools are fundamental settings for health education and adolescent females are an important group for promoting positive breast habits. We surveyed 2089 schoolgirls (11-18 years) to provide evidence for, and guidance on, breast education for schoolgirls. 26% reported negative feelings about their breasts and 87% reported ≥ one breast concern. 72% wanted to know more about breast cancer (69% rating this extremely important). >50% wanted to know more about breast sag and breast pain. Preferred delivery format … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Adolescence is a challenging time for girls; breasts and breast development can be embarrassing and confusing, negatively impacting body image, self-esteem (20), and physical activity participation (17). A survey of 2,089 school girls aged 11 to 18 years provided evidence of the need for, and guidance on breast education for this group (17,18). The majority (87%) of girls surveyed reported ≥ one breast concern such as how to check for breast cancer, breast bounce when exercising, breast pain, what boys think about girls' breasts, and how to find a bra that fits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescence is a challenging time for girls; breasts and breast development can be embarrassing and confusing, negatively impacting body image, self-esteem (20), and physical activity participation (17). A survey of 2,089 school girls aged 11 to 18 years provided evidence of the need for, and guidance on breast education for this group (17,18). The majority (87%) of girls surveyed reported ≥ one breast concern such as how to check for breast cancer, breast bounce when exercising, breast pain, what boys think about girls' breasts, and how to find a bra that fits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when surveying 2,089 girls, the majority (72%) reported wanting to know more about breast cancer, with 69% rating this topic as extremely important (1). Increasing adolescent girls' knowledge of the risks of breast cancer and benefits of early detection may improve breast cancer outcome and survival, and encourage these behaviors in adulthood when breast cancer risk is greater (18,29). Moreover, adolescent girls' body satisfaction and self-esteem may be improved by teaching them about breast sizes and shapes and how breasts change over time (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found the traditional method of a tape measurement to establish bra size to be unreliable, with this method overestimating the underband size in 76% of cases and underestimating the cup size in 84% of cases (White & Scurr, 2012). Literature now suggests that females should be educated on professional bra fitting criteria to improve their ability to independently choose a well-fitted bras (Brown et al, 2018;Boschma, Smith & Lawson, 1996;Chen et al, 2019;McGhee, Steele & Munro;White & Scurr, 2012), although to date limited research has investigated sizing methods employed when purchasing sports bras.…”
Section: Introductionmentioning
confidence: 99%
“…However, breast size is the most publicly visible breast dimension (Lynn, 2009) and plays an important role in body image (Grogan, Brownbridge, Kilgariff, & Whalley, 2012; Reaby, Hort, & Vandervord, 1994). In a survey of over 2000 female British adolescents aged 11 to 18 years, 87% reported at least one breast concern, with over a third reporting concerns about breast size (Brown et al 2017). These findings are concerning, yet unsurprising, if we consider how breast size is one of the main ways in which women’s breasts are objectified in popular culture (Seifert, 2005; Swami & Tovee, 2013; Tantleff-Dunn & Thompson, 2000).…”
mentioning
confidence: 99%